Timeliness and Contract Enforceability in Intermediate Goods Trade - Gamberoni, Elisa (2012)
This paper shows that the institutional environment and the ability to export on time are sources of comparative advantage as important as factors of production. In particular, the ability to export on time is crucial to explain comparative advantage in intermediate goods. These findings underscore the importance of investing in infrastructure and fostering trade facilitation to boost a country's participation in production networks. Furthermore, the paper contributes to the so-called "distance puzzle" by showing that the increasing importance of distance over time is in part driven by trade in intermediate goods.